2023
DOI: 10.1021/acs.analchem.3c02063
|View full text |Cite
|
Sign up to set email alerts
|

DpCoA tagSeq: Barcoding dpCoA-Capped RNA for Direct Nanopore Sequencing via Maleimide-Thiol Reaction

Abstract: Recent discoveries of noncanonical RNA caps, such as nicotinamide adenine dinucleotide (NAD + ) and 3′-dephospho-coenzyme A (dpCoA), have expanded our knowledge of RNA caps. Although dpCoA has been known to cap RNAs in various species, the identities of its capped RNAs (dpCoA-RNAs) remained unknown. To fill this gap, we developed a method called dpCoA tagSeq, which utilized a thiol-reactive maleimide group to label dpCoA cap with a tag RNA serving as the 5′ barcode. The barcoded RNAs were isolated using a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Studies have demonstrated that RNAs can be 5′-capped with metabolites, including dephospho-CoenzymeA (dpCoA), but identification of the capped RNAs is difficult. Recently, Shao et al developed a new method for detection of 5′dpCoA-capped RNA based on the reaction with maleimide linked to a oligonucleotide sequence tag and subsequent nanopore sequencing (dpCoA tagseq). The method was applied to RNA isolated from mouse liver, thereby leading to the identification 44 genes producing 5′dpCoA-capped RNA.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have demonstrated that RNAs can be 5′-capped with metabolites, including dephospho-CoenzymeA (dpCoA), but identification of the capped RNAs is difficult. Recently, Shao et al developed a new method for detection of 5′dpCoA-capped RNA based on the reaction with maleimide linked to a oligonucleotide sequence tag and subsequent nanopore sequencing (dpCoA tagseq). The method was applied to RNA isolated from mouse liver, thereby leading to the identification 44 genes producing 5′dpCoA-capped RNA.…”
mentioning
confidence: 99%
“…This is an interesting observation with many potential implications, but in most cases, the frequency of dpCoA capping observed for specific RNAs is likely to be low, making the identification of specific dpCoA-capped RNAs challenging. In a recent study, Shao et al developed the dpCoA-tagseq method and applied it to the detection of dpCoA-tagged RNA among RNA isolated from mouse livers . The dpCoA-tagseq method is based on specific addition of a maleimide containing 25 nt oligonucleotide sequence tag to the 5′ end of dpCoA-capped RNAs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In our recent paper, we reported the dpCoA tagSeq method for the identification of dpCoA-capped RNA (dpCoA-RNA). In this method, synthesized RNA containing thiol-reactive maleimide is used to label dpCoA-RNAs.…”
mentioning
confidence: 99%